Case Report: Fascioliasis Hepatica Precisely Diagnosed by Metagenomic Next-Generation Sequencing and Treated With Albendazole - Zhang, Yaling; Xu, Huan; Liu, Yi; Kang, Juan; Chen, Hairu; Wang, Zhiyi; Cai, Dachuan (Frontiers in Medicine, 2021)
The clinical manifestations of fascioliasis hepatica in humans are unspecific. Traditional diagnosis relies on evidence of live parasites or eggs in the bile or feces. However, due to similar imaging manifestations, they are often misdiagnosed as malignant tumors. Here, we report a case of a 43-year-old woman with fever and space-occupying liver disease. Liver biopsy, parasite-specific antibody screening, and stool testing did not find any pathogens. Therefore, metagenomic next-generation sequencing (mNGS) and routine microbiological examinations were performed. Finally, Fasciola hepatica was only identified by mNGS. The body temperature of the patient and the eosinophil count remained normal, and the space-occupying liver lesions were significantly absorbed after more than 7 months of treatment with albendazole. The details of this case highlight the timely use of mNGS to identify parasites and judge therapeutic effects after treatment, providing important help for clinical decision-making.